Restrição de crescimento induzida por estresse salino como uma estratégia de defesa oxidativa em raízes de feijão-caupi - Maia, Josemir Moura (2008)
In the present thesis, the hypothesis that the salt-induced impairment of root growth is due to changes in the symplastic and apoplastic antioxidant enzyme activity was investigated. Root growth impairment may be related to the enhancement and/or the control of the reactive oxygen species by enzymatic systems involved in growth regulation. This work was divided into five interconnected chapters. The first is a theoretical review of the approached subject and includes the scientific relevance of this study. This review details the oxidative mechanisms involved in root growth regulation under salinity, besides the signaling pathways activated under salt stress and related signaling molecules. In the chapter 2, the Pérola (sensitive) and Pitiúba (resistant) cultivars showing contrasting responses to salt stress at germination were evaluated during the seedling stage. Four-day-old seedlings were exposed to 100 mM NaCl for two days and it was determined the root length, dry weight, relative water content (RWC), Na+ content, K+/Na+ ratio and the activity of superoxide dismutase (SOD), ascorbate peroxidase (APX), phenol peroxidase (POX) and catalase (CAT). The obtained results were insufficient to categorize the tested cultivars as sensitive or resistant to salt stress at the seedling stage. The effect of the external NaCl concentration on the antioxidant responses in the studied cultivars was investigated in the chapter 3. It was assessed the root lenght, RWC, Na+ content and the activity of SOD, APX, CAT, and POX in seedlings treated with 0; 25; 50; 75 and 100 mM NaCl during two days. The root growth impairment was more pronounced in the Pitiúba cultivar under 100 mM NaCl. Additionally, it was verified that a metabolic network involving the POX activity could be associated with the maintenance of H2O2 levels and the root growth restriction. In the chapter 4, a time-course of the antioxidant responses were assessed in the Pitiúba cultivar. Then, the seedlings were exposed to 0, 50 and 100 mM NaCl during 0; 24; 48; 72; and 96 h and the same variables determined in the previous experiment were evaluated again. It was demonstrated that the root length reduction depends on the NaCl concentration and the time of exposure. Although the root Na+ content could suggest Na+ toxicity, no lipid peroxidation was detected. The involvement of SOD, APX, CAT, and POX activity in root growth regulation was minutely investigated in the chapter 5. Thus, the seedlings were exposed to salt stress in short- and long-term experiments. The reactive oxygen species metabolism in the apoplastic fraction was associated with the activity of NADPH oxidase (NOX), apoplastic SOD and cell wall POX. It is possible that oxidative stress and salt stress are interconnected as the antioxidant response could mimic the hypersensitive reaction. NOX, apoplastic SOD and cell wall POX showed enhanced activity preceding an oxidative burst. Additionally, H2O2 could act as an extracellular signal triggered by stress and play a role in cell wall strengthening.